Gauging Portuguese community pharmacy users' perceptions - Cavaco, Afonso (2007)
Objective: To assess perceptions related to facets of community pharmacy usage within the Portuguese general population. Methods: An ONSA (The Governmental Public Health Observatory) instrument was used, the ECOS (Em Casa Observamos Saúde) sample. This consisted of a national representative sample of household units with telephone. General demographics and pharmacy users’ perceptions related to five facets of community pharmacy usage were collected by telephone interviews. Main Results: Almost one-third (31.9%) of the participants were probable chronic drug users, hence in regular contact with the community pharmacy. Thirty-four percent preferred not to talk with the person who dispenses their prescribed drugs. Most users (47.6%) expressed opinions of pharmacists as being health care rather than business oriented, although one quarter of the sample was not sure. A large majority (73.7%) would like pharmacists to participate in their treatment decisions, but 55.1% did not seem able to distinguish between pharmacists and non-pharmacist technical staff, working at the pharmacy counter. Most significant predictors of users’ dichotomous perceptions related to the usage facets surveyed were age, education and occupation. Being older, less literate and economically inactive increased the odds of inappropriate users’ perceptions of the pharmacists. Conclusions: Results showed that erroneous concepts and behaviours exist within the Portuguese population in relation to the community pharmacists’ role. This is a matter for pharmacy professional and educational bodies to take into account when developing intervention strategies, in particular when communicating with the general public.